Strategi Pemasaran Komoditas Nanas (Annanas Comosus) Sebagai Produk Unggulan Kabupaten Mempawah - Putri Ayu; Yuni Firayanti; Marhamah, Marhamah (Jurnal Multidisiplin Indonesia, 2024)
Pineapple business in Indonesia has such high potential, so it is very suitable for pineapple business actors and farmers in Indonesia. Designing strategies and marketing methods for pineapple products is very important in increasing product sales. To meet public demand for pineapples, marketing activities are needed that can distribute the fruit from producers to consumers. Where marketing is essentially the flow of goods from producers to consumers. Marketing activities are an important factor that will determine the success of an entrepreneur. This study uses a qualitative research method by conducting a case study on the object being studied. The qualitative research method is a research method based on natural philosophy (experiment) where the researcher as an instrument, data collection techniques and data analysis are inductive/qualitative and emphasize meaning. Word of mouth marketing is a strategy that is more likely to be used by farmers in Peniraman village, because their customers come to their homes more so they can directly see the products they are going to buy. That's where farmers can run 4P marketing (product, price, place, promotion) by explaining the products they are going to sell and also bargaining for prices. Apart from that, Peniraman Village farmers also do marketing through earned media by creating Instagram stories via WhatsApp, Facebook.